A hybrid cementitious based-G/CFRP sandwich panel: concept, design and initial outcomes - Sena-Cruz, José (2018)
Nowadays, the advantages of using fibre-reinforced polymers (FRP) in Civil Engineering structures are very well-known. In comparison to other materials, the FRPs show high strength-to-weight and stiffness-to-weight ratios, as well as high corrosion resistance [1]. Moreover, they can be easily moulded into complex shapes during the manufacturing process. Due to the slenderness of the cross section components and systems [2], and their significant initial cost [3], the FRPs are typically used along with other materials in composite structural elements. In the recent years, the FRPs have been increasingly used in composite sandwich panels designed for the building and housing industry [4]. However, in terms of flooring solutions, the sandwich panels still reveal some limitations for the most typical values of spans and loads in buildings [5]. In order to overcome the aforementioned drawbacks, the EasyFloor project was launched to develop enhanced composite sandwich panels for rehabilitation of floors in buildings. One of the important innovations included in the project relies on the use of both glass and carbon fibre roving (G/CFRP). This hybrid solution aims at improving significantly both the strength and stiffness. Furthermore, the top face of the panel is made of steel fibre reinforced self-compacting micro concrete (SFRSCMC), instead of the usual FRP compressive face, aiming to overcome face wrinkling issues. Additionally, this solution can provide higher ductility, fire endurance and impact resistance [6]. Furthermore, polycianurate (PIR) closed-cell foam is used as core material of the panel. Proper adhesion between G/CFRP and SFRSCMC is developed in order to obtain the full bending capacity of the composite solution. Finally, the FRP component is produced by pultrusion, taking all the advantages of this manufacturing process. The final proposal for the hybrid sandwich panel was obtained through the use of genetic algorithms in the design, which consisted in optimizing the geometric and the mechanical properties of the panel, taking into account the following features: (i) structural and energy efficiency; (ii) durability, versatility of use, ease of handling, quick assembly and production; (iii) low maintenance needs and aesthetics. The present work describes the design solution that resulted from the optimization procedure and subsequently presents initial experimental results regarding the mechanical characterization of the different materials, as well as the FRP/SFRSCMC interface. The experimental program comprised: (i) tensile and flexural tests on both the bottom and external ribs of the C/GFRP laminate skins; (ii) tensile, compressive and direct shear tests on both foam core materials (PIR); (iii) compressive and flexural tests on the SFRSCMC top face, and; (iv) pull-off tests for the characterization of the connection between the SFRSCMC and FRP using different types of adhesives.